Perbandingan Kualitas Fermentasi Biji Kakao dengan Penambahan Kultur Campur dan Kultur Tunggal Lactobacillus brevis - Rannes Ran Nes; Andree Wijaya Setiawan; Yoga Aji Handoko (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Cocoa beans are one of the plants whose processing process is through fermentation to get quality cocoa beans. The purpose of this study was to determine the quality of fermented cocoa beans with the addition of mixed cultures of Saccharomyces cereviseae, Lactobacillus plantarum, Lactobacillus fermentum, Acetobacter orientalis, Acetobacter tropicalis, and single culture of Lactobacillus brevis and determine the best quality of fermented cocoa beans between mixed culture and single culture of Lactobacillus brevis. This study used a randomized block design with 7 treatments and 4 replications. Each treatment was carried out by adding a single culture and mixed culture in the logarithmic growth phase with a culture concentration of 5%, 10%, and 15%, and as a control, fermentation was conditioned to occur naturally. Observation parameters are pH, temperature, water content, yield, total fat content, total sugar content, lactic acid content, cut test, and organoleptic. The results of the fermentation showed that a good quality was obtained in the P5 treatment (addition of 10% mixed culture) which was perfectly fermented 94% and entered the quality class 1 of SNI 2323:2008. Keywords: cocoa, fermentation, mixed culture, single culture, Lactobacillus brevis